Risk Mitigation Strategy Based On Information Technology in Aircraft Maintenance Process (Case Study : PT MMF) - Rizky Angga Yusmahendra; Hana Catur Wahyuni (Procedia of Engineering and Life Science, 2022)
PT. Merpati Maintenance Facility is a company engaged in aircraft maintenance services. This company serves several types of aircraft maintenance such as Boeing and Airbus. In the process of aircraft maintenance at PT. Merpati Maintenance Facility Sidoarjo, to carry out maintenance in every job it must be in accordance with the Task Card the work made by PPC is based on the WO (Work Order), in the process of working on the task card, and it is often lost and creates data discrepancies, so PPC does not know the work that matches the task card been done or not. With the occurrence of these problems, it is necessary to measure the value of information technology using Technometrics methods to determine the value of TCC (Technology Contribution Coefficient) on each component of information system-based technology, as well as formulate risk mitigation strategies using the SWOT method. From the results of the study, the value of the company's TCC is 0.980. The results of the SWOT analysis position diagram for technoware, humanware, orgaware components in quadrant I and for infoware components in quadrant II. The results of the assessment of the contribution of this technology are associated with the strategic choice of aircraft maintenance services companies in the application of technology, which must always adjust to the speed of the latest technology. This adjustment effort is greatly assisted by the open availability of information. The purpose of the research is to determine the value of information system technology in the company. To provide a proposed mitigation strategy to correct weaknesses or deficiencies in the company.